Effect of dexmedetomidine infusion on hemodynamic responses in microsurgery of larynx - Shakuntala Basantwani; Mayuresh Patil; Balasaheb Govardhane; Jyoti Magar; Bharati Tendolkar (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Microlaryngeal surgery is a frequently performed ear, nose, and throat procedure used to diagnose and treat laryngeal disorders. Suspension laryngoscopy causes prolonged stimulation of the deep pressure receptors of the larynx leading to adverse circulatory responses and consequently cardiac complications. In this study, dexmedetomidine infusion was used to assess its effectiveness for attenuation of this hemodynamic stress response. Material and Methods: Sixty patients undergoing elective microlaryngeal surgery randomly received either dexmedetomidine 1 μg/kg over 10 min followed by continuous infusion of 0.5 μg/kg (Group D) or normal saline infusion at the same rate (Group P) till the end of surgery. Anesthesia in all patients was induced with propofol, succinylcholine to facilitate endotracheal intubation after premedication with fentanyl 2 μg/kg and glycopyrrolate. Intraoperative, vital parameters were maintained within 20% of baseline with rescue analgesic fentanyl 1 μg/kg and subsequently with propofol boluses up to 1 mg/kg. The percentage of patients and the total amount of intraoperative fentanyl and propofol required in each group were recorded. Sedation score at 10 minutes postextubation was assessed by Ramsay sedation score. Results: Intraoperative heart rate and mean arterial pressure in Group D were lower than the baseline values and the corresponding values in Group P (P > 0.05). The percentage of patients requiring rescue fentanyl and propofol was higher in Group P than Group D (36.6% and 30% vs. 6.6% and 3.3% P = 0.01). Recovery scores were better in dexmedetomidine group. Conclusion: Dexmedetomidine infusion attenuates the hemodynamic stress response during laryngoscopy, intubation, and microlaryngeal surgery and is associated better recovery profile.